2014
DOI: 10.1038/nmeth.2883
|View full text |Cite
|
Sign up to set email alerts
|

PyClone: statistical inference of clonal population structure in cancer

Abstract: We introduce a novel statistical method, PyClone, for inference of clonal population structures in cancers. PyClone is a Bayesian clustering method for grouping sets of deeply sequenced somatic mutations into putative clonal clusters while estimating their cellular prevalences and accounting for allelic imbalances introduced by segmental copy number changes and normal cell contamination. Single cell sequencing validation demonstrates that PyClone infers accurate clustering of mutations that co-occur in individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
1,052
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 884 publications
(1,083 citation statements)
references
References 23 publications
(20 reference statements)
8
1,052
0
1
Order By: Relevance
“…For example, SciClone (16) clusters the VAFs of SNAs in copy-number neutral and LOH-free portions of the genome using a Bayesian beta mixture model. Pyclone (15) is an extension of SciClone that adds prior information elicited from copy number estimates obtained from either genotyping arrays or WGS to its Bayesian nonparametric clustering method. Neither SciClone (16) nor Pyclone (15) infers the phylogenetic relationship between subclones.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, SciClone (16) clusters the VAFs of SNAs in copy-number neutral and LOH-free portions of the genome using a Bayesian beta mixture model. Pyclone (15) is an extension of SciClone that adds prior information elicited from copy number estimates obtained from either genotyping arrays or WGS to its Bayesian nonparametric clustering method. Neither SciClone (16) nor Pyclone (15) infers the phylogenetic relationship between subclones.…”
Section: Resultsmentioning
confidence: 99%
“…The existing methods differ by how this compensation is done. ABSOLUTE (13), EXPANDS (14), Pyclone (15), and PhyloSub (33) assume that, when a CNA event overlaps a SNA, the point mutation resides in a region with homogeneous aneuploidy, a scenario where no subclonal CNA events are allowed. Li and Li (19) conducted a detailed analysis of the complete set of scenarios covering the possible order and phase of overlapping SNAs and CNAs in developing their software CHAT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because cancer genomes constantly evolve under selective pressure, we investigated the extent of the human-to-mouse and mouse-to-mouse clonal dynamics using PyClone (Roth et al 2014;Eirew et al 2015), a method for estimating the proportion of cells in a tumor carrying each mutation and clustering them into subclones (groups of cells with the same genotype). We observed that most of the clones remained stable after engraftment and throughout passag- ing, although in certain instances some subclones increased or decreased their prevalence or even appeared or disappeared.…”
Section: Developing a Collection Of Patient-derived Tumor Xenograftsmentioning
confidence: 99%